Influence of fire on critically endangered Swartland Shale Renosterveld in the Cape Floristic Region. Issue 1 (30th December 2017) - Cousins, Stephen R.; Witkowski, Ed T. F.; Esler, Karen J.
Abstract: Questions: The degree to which renosterveld shrublands are fire‐dependent is currently unclear. To address this issue, the following questions were asked: (1) does smoke stimulate germination of soil‐stored seeds in renosterveld; (2) does recently‐burned renosterveld display changed composition and higher diversity than unburned vegetation; and (3) how do the species compositions of renosterveld soil seed banks and standing vegetation compare? Location: Swartland, Cape Floristic Region, South Africa. Methods: Soil seed bank samples from a north‐ and south‐facing slope were smoke‐treated and germinated to test for smoke‐stimulated germination. Burned standing vegetation was surveyed 16 months post‐fire, as was unburned vegetation on the same slopes. Seed bank species richness and density were compared between smoke‐treated and untreated samples within and between slopes. Burned and unburned standing vegetation were compared within and between slopes in terms of species richness, abundance and aerial cover. Compositional similarity of the seed banks and standing vegetation was assessed. Results: Seed banks were dominated by annuals and graminoids. Smoke treatment had no effect, except for driving significantly higher species richness and seedling density in south‐facing slope perennial shrubs. Species richness and seedling density were significantly higher in seed banks on the south‐facing slope compared to the north‐facing slope. Burned standing vegetation exhibited significantly higher diversity than unburned vegetation. Annuals and graminoids displayed significantly higher species richness and aerial cover in burned renosterveld. The north‐facing slope contained less than half the number of species/m 2 compared to the south‐facing slope. The seed banks and standing vegetation showed low to intermediate similarity (Sørensen = 31%–53%), but grouped close together on an NMDS plot, suggesting intermediate similarity overall. Conclusions: Elevated germination of perennial shrubs in smoke‐treated seed bank samples and increased diversity of post‐fire standing vegetation suggest the renosterveld in this study shows elements of a fire‐driven system. Certain species only recruited in burned sites, suggesting fire‐stimulated germination. Aspect had a major influence on plant community composition, with the mesic south‐facing slope being more diverse than the xeric north‐facing slope. The similarity between the seed banks and standing vegetation was higher than previously shown for renosterveld, and appears to be higher than for fynbos. Abstract : We investigated the extent to which renosterveld ‐ a critically endangered Mediterranean‐type shrubland ‐ is fire‐driven. Smoke treating soil seed banks had no effect, except for promoting germination in perennial shrubs. Diversity of burned standing vegetation was significantly higher than unburned vegetation. Certain species only recruited in burned areas suggesting fire‐stimulated germination. Fire therefore appears to be important, but the vegetation displays weaker fire‐dependency than fynbos shrublands.